Remote Home Visit: Exploring the feasibility, acceptability and potential benefits of using digital technology to undertake occupational therapy home assessments. (October 2020) - Read, Jennifer; Jones, Natalie; Fegan, Colette; Cudd, Peter; Simpson, Emma; Mazumdar, Suvodeep; Ciravegna, Fabio
Introduction: Home assessments are integral to the occupational therapy role, providing opportunities to personalise and integrate care. However, they are resource intensive and declining in number. A 3-month service development within one United Kingdom National Health Service acute hospital setting explored the concept of using digital technology to undertake remote home assessments. Methods: Four work streams explored the concept's feasibility and acceptability: real-world testing; user consultations; narrative case study collection; traditional visit resource use exploration. Project participants were occupational therapists and patient and public representatives recruited via snowball sampling or critical case sampling. Qualitative data were thematically analysed identifying key themes. Analysis of quantitative data provided descriptive statistics. Findings: The remote home visit concept was feasible within four specific contexts. Qualitative themes suggest acceptability depends on visitor safety, visitor training, visitor induction and standardisation of practice. Consultees perceived the approach to have potential for resource savings, personalisation and integration of care. Barriers to acceptance included data security, data governance, technology failure and threat to occupational therapists' role and skills. Conclusion: Applying digital technology to occupational therapy home assessment appears feasible and acceptable within a specific context. Further research is recommended to develop the technology, and test and investigate perceived benefits within wider contexts and stakeholder groups.